Residents’ Social Interactions in Market Square and Its Impact on Community Well-Being - Oluwagbemiga Paul Agboola; Mohd Hisyam Rasidi; Ismail Bin Said; Solomon Dyachia Zakka; Abdul-Wahab Shuaibu (Journal of Contemporary Urban Affairs, 2018)
This study aims at ameliorating the associated challenges emanated from the ineffective planning, management and design of market square as well as appraisal of the interactions among people of diverse ethnicity. Hence, the study explores users’ interactions and activities within three markets square in rural neighborhoods of South-west, Nigeria. The significant relationship between resident’s interactions and the community well-being was explored. Consequently, this study highlights the influence of the market square as a typical neighborhood open space on residents’ well-being. The study’s quantitative approach encircled the purposive structured survey questionnaire data obtained from Yorubas, Hausas, and Ibos respondents (n=382); and analyzed by SPSS statistical package (version 22). Meanwhile, the qualitative data included observation of various activity pattern among the three ethnic groups. The study’s findings revealed that an improvement in the market square quality becomes necessary in order to increase residents’ interactions and well-being. Also, the study elucidates the appropriate link between the built environment, residents’ interactions, and well-being. It is concluded that residents’ well-being is a reflection of an experience manifested within the interplay of individuals and groups’ social interactions. This study of people and place relationships could better equip the professionals in the built environment on the importance of creating a sustainable open space towards improving residents’ well-being and rural community revitalization efforts.